Les réactions de la doctrine à la création du droit civil québécois par les juges : les débuts d'une affaire de famille - Jobin, Pierre-Gabriel (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1980)
The middle of the twentieth century marked a turning point in the history of scholarly writings on the civil law in Québec. The emergence of a full-time teaching body in the law faculties entailed consequences of primary importance: publications gained not only in quantity, but also in quality and diversity and, in particular, the reactions of legal writers to judge-made law became frequent and substantial. The relations between legal writers and judges illustrate, here as elsewhere, the particular situation of the Québec legal system at the crossroads of civil law and common law. For instance, due to the British-inspired method of appointing judges and some local traditions, judges are personally known to many professors. Furthermore, decisions of the courts, most of the time, are written in a learned style, the merits of the legal issues being discussed and doctrinal opinions being quoted with approval or criticism. These relations between the writers and the judiciary may explain the great interest of legal writers in judge-made law and their perhaps insufficient sense of critical responsibility vis-à-vis that law. Legal writers and judges have the great advantage of speaking the same language and of maintaining a dialogue — an advantage which benefits law itself and the whole community.